Cis-acting elements distinct from the 5' splice site promote U1-independent pre-mRNA splicing. - Crispino, J D (1996)
We have identified a class of pre-mRNAs that are spliced in HeLa extracts depleted for U1 snRNP (delta U1 extracts). Previously, we described pre-mRNAs that can be spliced in delta U1 extracts only when high concentrations of SR splicing factors are added. In contrast, the substrates characterized here are efficiently processed in delta U1 extracts without the addition of excess SR proteins. The members of this class comprise both a naturally occurring pre-mRNA, from the Drosophila fushi tarazu gene, and a chimera containing sequences from two different pre-mRNAs that individually are dependent upon U1 snRNP or excess SR proteins. Several sequence elements account for the variations in dependence on U1 snRNP and SR proteins for splicing. In one pre-mRNA, a single element was identified adjacent to the branch site. In the other, two elements flanking the 5' splice site were found to be critical. This U1-independent splicing reaction may provide a mechanism for cells to control the extent of processing of different classes of pre-mRNAs in response to altered activities of SR proteins, and furthermore suggests that U1 snRNP-independent splicing may not be uncommon.